Security in Wireless Sensor Networks: A Cryptography Performance Analysis at MAC Layer - Mauro Tropea; Mattia Giovanni Spina; Floriano De Rango; Antonio Francesco Gentile (Future Internet, 2022)
Wireless Sensor Networks (WSNs) are networks of small devices with limited resources which are able to collect different information for a variety of purposes. Energy and security play a key role in these networks and MAC aspects are fundamental in their management. The classical security approaches are not suitable in WSNs given the limited resources of the nodes, which subsequently require lightweight cryptography mechanisms in order to achieve high security levels. In this paper, a security analysis is provided comparing BMAC and LMAC protocols, in order to determine, using AES, RSA, and elliptic curve techniques, the protocol with the best trade-off in terms of received packets and energy consumption.